Development of a 19‐plex short tandem repeat typing system for individual identification and parentage testing of horses (Equus caballus). (15th July 2021) - Shang, S.; Jiang, R.; Luo, R.; Jia, S.; Irwin, D. M.; Wang, Z.; Zhang, S.
Summary: Individual identification of horses for pedigree verification and registration is important for the sustainable development of the horse industry. Horse individual identification and parentage tests commonly use the 17 short tandem repeats (STRs) recommended by the International Society for Animal Genetics (ISAG) and the locus LEX33. While many multiplex STR typing systems have been established for the horse, a sex determining marker is usually absent, and none of them can simultaneously detect all 17 ISAG recommended loci and the locus LEX33. Here, we present a 19‐plex STR typing system that contains the 17 ISAG recommend loci, the locus LEX33 and amelogenin as sex determining loci. The results of our sensitivity, species specificity, stutter analysis and population data analysis, indicate that this system is a specific, sensitive, and robust tool for the identification of individuals, parentage testing and genetic research in the horse.